L1 vowels of multilinguals: the applicability of SLM in multilingualism - Sypiańska, Jolanta (Research in Language, 2016)
Although L1 has been treated as a rigid system which is more likely to act as a sender than a receiver of CLI in bilinguals and multilinguals, recent studies have provided some evidence of the influence of both L2 and L3 on L1. The study is aimed at shedding further light on how Lns can influence the native language and how these changes can be explained by means of the Speech Learning Model. The first and second formant of L1 Polish vowels of three groups of multilinguals were compared. Evidence of a systemic influence of L2 on L1 was observed in the raising and backing of L1 Polish vowels due to L2 English and lowering and backing or fronting of L1 Polish vowels due to L2 German. No systemic influence of L3 on L1 was observed. The predictions derived from equivalence classification of SLM were tested for the Polish vowel /ɛ/ and the closest vowels from Lns. The majority of predictions regarding the convergence or divergence of the particular diaphone were supported by the data.